2009
DOI: 10.1111/j.1464-410x.2009.08681.x
|View full text |Cite
|
Sign up to set email alerts
|

Living‐donor renal transplantation of grafts with incidental renal masses after ex‐vivo partial nephrectomy

Abstract: metastatic evaluation. After laparoscopic donor nephrectomy a back-table partial nephrectomy was performed and frozensection analysis was used to confirm both the diagnosis and negative surgical margins before transplantation. RESULTSRenal cell carcinoma was found in three of the five masses (one each cystic, clear cell and papillary; Fuhrman grades II, II and III, respectively) and the other two patients had angiomyolipoma. There were no long-term complications in the transplanted kidneys. One patient develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Excision of such tumors, including angiomyolipomas, does not seem to affect graft or recipient survival [24,25]. The exact size thresholds delineating when to excise angiomyolipomas are unclear, although angiomyolipomas larger than 5 mm may warrant surgical excision [26]. At our institution, angiomyolipomas, regardless of their size, direct the transplant surgeon toward using the affected kidney for donation.…”
Section: Mri Characterization Of Lesions In Donor Kidneysmentioning
confidence: 86%
“…Excision of such tumors, including angiomyolipomas, does not seem to affect graft or recipient survival [24,25]. The exact size thresholds delineating when to excise angiomyolipomas are unclear, although angiomyolipomas larger than 5 mm may warrant surgical excision [26]. At our institution, angiomyolipomas, regardless of their size, direct the transplant surgeon toward using the affected kidney for donation.…”
Section: Mri Characterization Of Lesions In Donor Kidneysmentioning
confidence: 86%
“…9 However, attitudes towards this have changed in individuals with no prior stone history and those with a negative metabolic workup. Our results corroborate the findings of several studies that have demonstrated the safety and ease of performing ex-vivo ureteroscopy prior to renal implantation.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, few series have been described using grafts with small renal tumor after bench surgery excision. Sener et al (14) published their series of five kidney transplant recipients with kidneys with incidentally diagnosed renal mass before implantation in live related donors. Three of them were small and low-grade RCC.…”
Section: Discussionmentioning
confidence: 99%